ANALISIS FATWA MUI TENTANG LARANGAN PENGGUNAAN ATRIBUT NATAL BAGI MUSLIM : SEBUAH PRAKTIK ANALISIS WACANA KRITIS - Yoyok Sabar Waluyo (Politeknik Negeri Jakarta, 2018)
AbstractThis article tries to present and explore a response of PP Muhammadiyah to MUI’s fatwa about freedom and comfortable worship in approaching the Christmas Day. The news text is published online media of Republika.co.id dated November 21st, 2016. The fatwa states that moslems are banned using attribute of celebrating the Christmas Day. This regards for giving a right of belief conducting. The issue causes some differences responses among people and organizations. The text will be explored using a critical discourse analysis in the viewpoint of systemic functional linguistic approach to analysis. This article uses a descriptive – qualitative method to make obvious and easy in understanding the analysis. This article found some data, i.e. words and clauses representing the aims and function of the fatwa, as well as a critic. The data conveys the proven that the fatwa is on the right track to reveal the freedom and comfortable worship. This article exposes the argument and suggestion following the fatwaKeywords: CDA, SFL, freedom, comfortable worship, fatwa, moslemAbstrakPenelitian ini dilalukan berdasarkan penelitian sebelumnya yang dilakukan pada tahun 2010 yang berjudul “Kekerapan Penggunaan Kosakata Bahasa Inggris Teknik yang digunakan Mahasiswa Jurusan Teknik Elektro”. Penelitian ini dibertujuan untuk memfasilitasi mahasiswa untuk berlatih kosakata bahasa Inggris Teknik. Karena hasil penelitian ini berupa perangkat lunak maka perangkat ini dapat digunakan kapan saja dan dimana saja. Perangkat ini terdiri dari 3 bagian latihan. Dan pada akhirnya diberikan hasil evaluasi dengan sistem penilain. Hal ini akan memotivasi mahasiswa untuk belajar lebih giat lagi.Kata Kunci: kosakata bahasa Inggris teknik, perangkat lunak, mudah dibawa